Culinary Turn Aesthetic Practice of Cookery - van der Meulen, Nicolaj; Wiesel, Jörg (Ästhetische Praxis, 2017)
Kitchen, cooking, nutrition, and eating have become omnipresent cultural topics. They stand at the center of design, gastronomy, nutrition science, and agriculture. Artists have appropriated cooking as an aesthetic practice - in turn, cooks are adapting the staging practices that go with an artistic self-image. This development is accompanied by a philosophy of cooking as a speculative cultural technique. This volume investigates the dimensions of a new culinary turn, combining for the very first time contributions from the theory and practice of cooking.